Metabolic triggers of invariant natural killer t-cell activation during sterile autoinflammatory disease - Riffelmacher, T; Kronenberg, M (Begell House, 2020)
Ample evidence exists for activation of invariant natural killer T (iNKT) cells in a sterile manner by endogenous ligands or microbial antigens from the commensal flora, indicating that iNKT cells are not truly self-tolerant. Their controlled autoreactivity state is disturbed in many types of sterile inflammatory disease, resulting in their central role in modulating autoimmune responses. This review focuses on sterile iNKT-cell responses that are initiated by metabolic triggers, such as obesity-associated inflammation and fatty liver disease, as a manifestation of metabolic disease and dyslipidemia, as well as ischemia reperfusion injuries and sickle cell disease, characterized by acute lack of oxygen and oxidative stress response on reperfusion. In the intestine, inflammation and iNKT-cell response type are shaped by the microbiome as an extended "self". Disease- and organ-specific differences in iNKT-cell response type are summarized and help to define common pathways that shape iNKT-cell responses in the absence of exogenous antigen.